Peace Education Taught by the Female Muslim Nobel Peace Prize Laureates in 21st Century - Supaat, Supaat; Suciati, Suciati (UIN Sunan Kudus, 2020)
AbstractWomen have a very important role in upholding world peace and security because they have the power that is not possessed by men, namely the maternal instinct which naturally can create peace with love, care and harmony. This study aims to find out Muslim women who received world peace awards in the 21st century and analyze the points of peace education that they teach and implement. This research was a qualitative descriptive study with the content analysis of the peace speech they deliver. Based on the analysis, it can be seen that there are three Muslim women who received world nobel peace prize in the 21st century, namely Shirin Ebadi, Tawakkul Karman and Malala Yousafzai. The messages of peace that become their focus are efforts for democracy and human rights, especially the struggle for human rights and children (Shirin Ebadi), nonviolent struggle against women's security and women's human rights for full participation in peace-building work (Tawakkul Karman), struggle against the oppression of children and young people and the right of all children to get education (Malala Yousafzai).